Making the agriculture sector work for youth: A tool to promote young men and women’s engagement in growing root, tuber and banana crops - Mudege, Netsayi N.; Mbiri, D.; Mdege, N. (International Potato Center, 2019)
Using data gathered from projects implemented by the International Potato Center (CIP) and the CGIAR Research Program on Roots, Tubers and Bananas, this paper first seeks to debunk some common myths and highlights ways to engage young men and women in agriculture in ways that are beneficial to them. It also proposes a tool, consisting of a checklist of questions, that could be used by agriculture research and development practitioners to help them ensure their agricultural projects in Africa effectively engage with youth, with a focus on root, tuber and banana (RTB) crops.